Risk Factors and Control Strategies for Cattle Tick Infestations in Nigeria: Influence of Acaricide Application Methods, Hand-Picking Frequency, and Herd Mobility in Plateau State - Biallah Markus Bukar; Uchechukwu C. Ohaeri; Henry Madubuike; Gloria Karaye; Mark Kparmark; Davwet Benkaat Maxwell; Goni Dogo Abraham (Journal of Parasite Research, 2025)
Background Tick infestations severely impair cattle health and productivity in Nigeria through blood loss, hide damage, and transmission of tick-borne pathogens. Objective This study assessed key risk factors influencing tick infestation and evaluated control methods among Fulani pastoral herds in Plateau State. Methods A cross-sectional survey involving 250 cattle from ten herds was conducted across five Local Government Areas. Tick burden was analyzed against acaricide application methods (pour-on vs. hand-spray), hand-picking frequency, and herd mobility (sedentary vs. migratory). Data were collected via owner interviews and manual tick counts. Statistical analyses were performed using generalized linear models in R software. Results Cattle treated with pour-on acaricides had significantly lower tick burdens compared to those treated via hand-spray (P<0.05). Herds that practiced hand-picking five times weekly had fewer ticks than those hand-picking thrice weekly (P<0.01). Migratory herds recorded significantly lower infestations than sedentary herds (P<0.05). Conclusion Effective tick control requires the integration of optimized acaricide application, frequent manual removaland consideration of herd mobility patterns. Education, capacity building, and policy support are necessary to enhance adoption of effective tick control measures among pastoralists.
Keywords: cattle ticks